PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN PENGUASAAN KONSEP MAHASISWA CALON GURU BIOLOGI - Samsuri, Taufik; Fitriani, Herdiyana (Bioscientist : Jurnal Ilmiah Biologi, 2016)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><p class="MsoNormal" style="margin-bottom: .0001pt; text-align: justify; line-height: normal; tab-stops: 45.8pt 91.6pt 137.4pt 183.2pt 229.0pt 274.8pt 320.6pt 366.4pt 412.2pt 458.0pt 503.8pt 549.6pt 595.4pt 641.2pt 687.0pt 732.8pt;">Abstract: A research has been conducted to improve the mastery of students of biology teacher candidates through the application of inquiry learning model. This type of research is a classroom action research. This research applied to FPMIPA biology education student of IKIP Mataram, on the subject matter of plant structure and development. The results showed that 91% of students declared complete study on cycles II and 65% of students declared complete in sikus I. Thus the increase in mastery of the concept is in the high category. Based on the results of data analysis can be concluded that biology learning on the subject matter of structure and development of plants with inquiry model can improve the mastery of the concept of biology teacher candidates. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>